"Covid‐19 is dangerous": The role of parental verbal threat information on children's fear of Covid‐19. Issue 1 (25th October 2022) - Nimphy, Cosima A.; Elzinga, Bernet M.; Van der Does, Willem; Aktar, Evin
Abstract: Introduction: Theoretical and empirical evidence suggests that the effect of parental verbal threat information on the offspring's fear acquisition of novel stimuli may be causal. The current study investigated this verbal fear acquisition pathway from parents to children in the unique context of Covid‐19 as a novel environmental threat for parents and children. Methods: Using an online cross‐sectional survey, we collected data about fear of Covid‐19, parent–child communication, parental anxiety, and child temperament, in the period between June 11th 2020 and May 28th 2021. Participants were 8 to 18‐year‐old children ( N  = 195; M age  = 14.23; 113 girls) and their parents ( N  = 193; M age  = 47.82; 146 mothers) living in the Netherlands. Results: Children of parents with stronger Covid‐19 fears also reported stronger Covid‐19 fears. Moreover, parents who were more fearful of Covid‐19 provided more threat‐related information about the virus to their children. More parental threat information in turn was related to stronger fear of Covid‐19 in their children, and partly mediated the link between parent and child fear of the virus. The link between parental threat information and children's fear of Covid‐19 was not moderated by child temperament or parental anxiety. Conclusions: Parental communication about Covid‐19 may play a role in children's fear acquisition of Covid‐19. The lack of moderation of this link by parental anxiety and child temperament may reflect the potentially adaptive nature of verbal fear transmission during the first year of the pandemic and the nonclinical levels of fear in this community sample.